1.74 Ga crustal melting after rifting at the northern Indian margin: investigation of mylonitic orthogneisses in the Kathmandu area, central Nepal. Issue 10 (3rd July 2019) - Imayama, Takeshi; Arita, Kazunori; Fukuyama, Mayuko; Yi, Keewook; Kawabata, Ryoichi
ABSTRACT: Mylonitic orthogneisses in the Kathmandu area, central Nepal have been investigated using whole-rock and mineral chemistry, Rb-Sr isotopes, and zircon U-Pb age dating. Zircon REE patterns determined from orthogneisses are characterized by enriched HREE patterns and the prominent Eu anomalies, consistent with a magmatic origin. The U-Pb zircon age dating and Ti-in-zircon thermometry revealed crystallization took place ca. 1.74 Ga at temperatures of 705–765℃; typical of felsic magmatism in the crust. Whole-rock data from most orthogneisses in this study and from similar rocks in previous studies span the 'syn-collisional' and 'post-collisional' fields on various tectonic discrimination diagrams, while some data also plot in rift-related magmatism fields. The peraluminous compositions, very high Sr isotopic ratios (0.865–3.585) and high Th and U concentrations for all orthogneisses in this study indicate that mylonitic orthogneisses are largely of S-type crustal origins. The new data presented herein, combined with that of previous studies, outline at least two Palaeoproterozoic magmatic episodes: 1) ca. 1.92–1.90 Ga rift-related magmatism derived from mantle melting and 2) 1.84–1.74 Ga crustal melting, resulting from burial of the Indian basement during thermal subsidence after rifting. This two-stage Palaeoproterozoic magmatism in Nepal occurred along the northern passive margin of the Indian basement during and/or after the breakup of the Columbia supercontinent.